The Influence of Managerial Communication, Workload, and Compensation on Turnover Intention with Job Satisfaction as a Mediation Variable on XYZ Insurance Employees in Tangerang - Pandia, Nadia Erlikasna B. R.; Ardi, Ardi; Sunarjo, Richard Andre (Syntax Literate, 2024)
This study aims to determine the influence of managerial communication, workload, and compensation on turnover intention, with job satisfaction serving as a mediating variable. The study was conducted at the XYZ Insurance office in Tangerang, involving 138 employees, with sample size determined using the Krejcie-Morgan formula and purposive sampling method. Data was collected through questionnaires distributed via Google Forms, containing 40 questions with 1-5 Likert scale. The data was analyzed using the partial least squares structural equation modeling (PLS-SEM) method. The results indicate that managerial communication, workload, and compensation negatively affect turnover intention among XYZ Insurance employees. Furthermore, the study demonstrates that job satisfaction mediates the relationship between managerial communication, workload, and compensation on turnover intention.